2018
DOI: 10.1021/acs.jafc.7b05603
|View full text |Cite
|
Sign up to set email alerts
|

Red Walnut: Characterization of the Phenolic Profiles, Activities and Gene Expression of Selected Enzymes Related to the Phenylpropanoid Pathway in Pellicle during Walnut Development

Abstract: A rare walnut variant with a red seed coat (pellicle) was examined for alterations in its phenolic profile during development. The red-walnut (RW) pellicle was compared with two commonly colored walnut varieties: 'Lara' (brown) and 'Fernor' (light brown). Furthermore, the activities of selected enzymes of the phenylpropanoid- and flavonoid-related pathways and the relative expressions of the structural genes phenylalanine ammonia lyase ( PAL) and anthocyanidin synthase ( ANS) were examined in the pellicles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Several genes related to SM showed differential expressions when lotus root was subjected to long-term storage (e.g., those related to PAL, POD, 4CL, CHS, CSE, and COMT; Table 1: S7), which suggested that high SM-related gene expressions promoted the activity of relevant enzymes leading to an increase in phenolic compounds derived from the phenylpropanoid pathway. This result is consistent with other studies on browning in fresh-cut fruits and vegetables (Hisaminato et al 2014;Persic 2018;Liu et al 2018). Furthermore, a number of lipid and membrane related DEGs identified by the GO distribution encoded key enzymes involved in fatty acid biosynthesis and the lipid degradation pathways (Table 1; Fig.…”
Section: Functional Annotation and Classification During Browning Development In Intact Lotus Rootsupporting
confidence: 93%
“…Several genes related to SM showed differential expressions when lotus root was subjected to long-term storage (e.g., those related to PAL, POD, 4CL, CHS, CSE, and COMT; Table 1: S7), which suggested that high SM-related gene expressions promoted the activity of relevant enzymes leading to an increase in phenolic compounds derived from the phenylpropanoid pathway. This result is consistent with other studies on browning in fresh-cut fruits and vegetables (Hisaminato et al 2014;Persic 2018;Liu et al 2018). Furthermore, a number of lipid and membrane related DEGs identified by the GO distribution encoded key enzymes involved in fatty acid biosynthesis and the lipid degradation pathways (Table 1; Fig.…”
Section: Functional Annotation and Classification During Browning Development In Intact Lotus Rootsupporting
confidence: 93%
“…Transcription analysis revealed that JrPAL was expressed in all tested tissues including roots, stems, and leaves, with the highest transcription level found in roots [31]. From June to September, the related JrPAL expression was most pronounced in August, indicating a high synthesis rate of phenolic compounds at this development stage in different varieties of J. regia [33]. In black walnut ( J. nigra ), PAL genes were also strongly expressed in autumn, suggesting that their transcription in these tissues contributes to phenolic biosynthesis [34].…”
Section: Introductionmentioning
confidence: 99%
“…After various extraction procedures, the samples were centrifuged and filtrated through 0.20 μm Chromafil AO-20/25 polyamide filters (Macherey-Nagel, Düren, Germany) into vials. The samples were further analyzed by the protocol described in Persic et al (2018). The determination of individual phenolics was carried out on a Thermo Finnigan Surveyor high-performance liquid chromatography system (HPLC, Thermo Fisher Scientific, Waltham, USA).…”
Section: Phenolic Compounds Analysis By Hplc-msmentioning
confidence: 99%